Impact Of Foodalyzer© Application On Knowledge, Attitude, And Perception Towards Selecting Commercial Eateries To Prevent Foodborne Disease - Umi Kalsom Md Ariffin; Shamarina Shohaimi; Wen-Li Seow; Abdul Rahman Mohamad Gobil; Noris Mohd Norowi; Nor Afiah Mohd Zulkefli; Tengku Zetty Maztura Tengku Jamaluddin; Roshariza Idris; Shing Wei Ng; Syafinas Amin-Nordin; Nurul Azmawati Mohamed @ Abd Aziz; Madihah Mohd Saudi (Elsevier, 2024)
Indexed by WOS/Scopus/ERA